Studi Adsorpsi-Desorpsi Anion Fosfat Pada Bentonit Termodifikasi CTAB - Adawiah, Syarifah Rabiatul; Sutarno, Sutarno; Suyanta, Suyanta (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2020)
Adsorption-desorption studies of phosphate on CTAB modified bentonite have been investigated. The results were characterized by FT-IR spectrometer to determine the functional groups in bentonite and X-ray diffractometer to determine the type of minerals in the bentonite. Adsorption was conducted by shaking 10 mg adsorbent in 5 mL adsorbate solution at the optimum condition of pH, contact time, and concentration. Furthermore, desorption studies were conducted on 5 mL medium of both water and citric acid 0.33 M and using 6.5 mg of adsorbent which has adsorbed phosphate. The results showed that the bentonite has been successfully modified with CTAB. The adsorption capacity of phosphate is 0.028 mmol g-1. Desorption studies showed that the solubility percentage of phosphate anion in citric acid was 0.33 M (73.33%) greater than in water (57.81%) which is a requirement for the use of slow-release fertilizers (SRF).